Intramedullary Spinal Capillary Hemangioma: Case Report - Welling, Leonardo; Welling, Mariana S.; Figueiredo, Eberval G. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Capillary hemangiomas involving the neuraxis are very uncommon. In the spinal cord, they are located mainly intradural and extramedullary. To our knowledge, only four cases in conus medullaris have been previously described. In our case, a 46-year-old man was admitted with back pain, sphincter disturbances, as well as progressive weakness and numbness on the lower extremities. Magnetic resonance imaging revealed an undefined intramedullary lesion on the conus medullaris. The patient underwent microsurgery, which achieved complete removal. Histopathological diagnosis was compatible with capillary hemangioma. His postoperative course was uneventful and all symptoms, including bladder dysfunction clearly regressed. The treatment of intramedullary capillary hemangiomas is very critical in preventing unnecessary morbidity, providing accurate information with respect to prognosis, and establishes a regular outpatient follow-up. The natural history of this lesion involving the spinal cord is not well described, although they are common elsewhere in the body.
Keywords: intramedullary; spinal; tumor